Pengaruh Terapi Tertawa Terhadap Depresi Pada Usia Lanjut - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
Background: The improvement of life expectation has more impact to the happening of diseases at the elderly, the biggest one is depression. One principle which must be paid attention to lessen the stress and depression is laughing. Laugh can lessen epinefrin and kortisol, and also can stimulate secretion of endorphin. Objective: Knowing if there was any influence of laugh therapy to depression at the elderly in Wirosaban RW XIV Sorosutan Umbulharjo Yogyakarta. Method: This research used experiment method with design of control group pretest-posttest. Instruments used were Geriatric Depression Scale (GDS), Short Portable Mental Status of Questionnaire (SPMSQ) and game standard of Sumarni (2001). This research was conducted in July until September 2004 with control group sample counted 8 responders and experiment group counted 8 responders. Experiment group was given laugh therapy with twice game in one week while control groups were not given. Result: Statistical analysis with paired t test showed the significance result of experiment group with p=0,000 and p=0,007 with depression mean before experiment 8,125, mean after first experiment 5,750 and after second experiment 5,875 meaning there was a decrease of depression level score 2,375 and 2,250. While control group showed result which did not have a significance, with p=0,451 and p=0,351 with depression mean before experiment 8,250, mean after first experiment 8,500 and after second experiment 8,000 meaning there was an increase of 0,250 and decrease of 0,250. This matter was caused by environmental influence. Level of pretest depression at group control and experiment group were mild depression of 62,5% and medium until severe depression of 37,5%. Level of depression at experiment group for the posttest 1 and posttest 2 were not depression of 50% and 37,5%, mild depression of 37,5% and 50%, and medium until severe depression of 25%. Level of depression at control group for the posttest 1 and posttest 2 were not depression of 12,5%, mild depression of 50%, and medium until severe depression of 37,5%. Conclusion: Level of depression before laugh therapy was done mostly was mild depression. Level of depression after laugh therapy was done mostly was not depression and mild depression. There was a significance differences before and after the laugh therapy was done. Experiment groups decreased in mild depression and medium until severe depression, while control groups decreased only in mild depression. There was an influence of laugh therapy to the depression in elderly.